Heptaphosphide cluster anions bearing group 14 element amide functionalities. - Quintero, G; Paterson-Taylor, I; Rees, N; Goicoechea, J (Royal Society of Chemistry, 2016)
Reactions of the protonated heptaphosphide dianion, [HP7](2-), with one equivalent of E[N(SiMe3)2]2 (E = Ge, Sn, Pb) give rise to novel derivatized cluster anions [P7EN(SiMe3)2](2-) (E = Ge (1), Sn (2) and Pb (3)). All three species were characterized by multi-element solution-phase NMR spectroscopy and electrospray ionization mass spectrometry. In addition, 1 and 2 were structurally authenticated by means of single crystal X-ray diffraction in [K(18-crown-6)]2[P7EN(SiMe3)2]·2py. Interestingly, while 2 appears to be indefinitely stable in solution for prolonged periods of time, the germanium-containing analogue, 1, readily decomposes at room temperature giving rise to the dimeric species [(P7Ge)2N(SiMe3)2](3-) (4) and [K(18-crown-6)][N(SiMe3)2]. A low quality single crystal X-ray structure of the former allowed for the confirmation of its composition and connectivity which is consistent with the (31)P NMR spectrum obtained for the anion.